Investigation of Effect of Adding Hydrophobically Modified Water Soluble Polymers on the Structure and Viscosity of Anionic Vesicle Dispersion - Marco Sandjaja; Maria Lucia Ardhani Dwi Lestari (Universitas Gadjah Mada, 2017)
This present study was conducted to investigate the effect of adding hydrophobically modified end-capped (HM) polymers with various polyethylene oxide (PEO) chain lengths on the structure and viscosity of anionic vesicles dispersion. A pronounced increase in viscosity was observed upon adding small amount of such polymers. Based on the dynamic light scattering (DLS) and small angle neutron scattering (SANS) analysis, 10 to 30 polymer molecules per vesicles can reach maximum viscosity and where polymer molecules can interconnect the vesicles without disrupting their structure. In addition, the kinetic stability of the vesicle dispersion also enhanced. From the measurement of the electrical conductivity of the dispersion, it was observed that the presence of the PEO and polypropylene oxide (PPO) group could induce the permeability of the vesicle membrane by altering their internal structure. Controlling viscosity of vesicles dispersion without changing its structure is useful for the further application of vesicles system such as in drug delivery, cosmetics and biomedical.